Evaluation of the design and methodology of applications to the local ethics committee - ELÇİOĞLU, HATİCE KÜBRA (My University, 2021)
Objectives: Proposals for scientific studies must have an original hypothesis and the appropriate design and methodology to test the premise. Methods: This study is an evaluation of the suitability of applications submitted to a local ethics committee (EC) and the rate of publication of that research. Results: A total of 899 files submitted for EC approval were retrospectively assessed. The EC found that the description of the methods in 44% of the applications was inaccurate, and that this type of error was most often seen in submissions from the surgical branch. In all, 52% of the applications for which we were informed about their final status were not published. Conclusion: The results suggest that improved training in epidemiology is required to reduce the number of application errors and that new regulations could help to motivate healthcare personnel to conduct scientific research and publish their findings. Keywords: Case-control study; epidemiology; ethics committees; interventional studies; research misconduct; thesis studies
Keywords: TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Case-control study; epidemiology; ethics committees; interventional studies; research misconduct; thesis studies